Unraveling the intriguing potential of protein-rich microbial biostimulants for horticultural crops - Kiruba Kalimuthu; Kumutha K; Sabarinathan K.G; Vijaya Priya P; Mini M.L; Amutha R (Plant Science Today, 2024)
Nutritional security and minimizing the impact of farming practices on the environment are major challenges in modern farming systems. Currently, the horticulture sector is growing fast and moving towards sustainability and profitability. Indiscriminate and improper use of chemical inputs to ensure high yields of horticultural products could lead to significant contamination of soil and water bodies. Under these circumstances, farmers must optimize their input management to reduce pollution and preserve the economic margin by following sustainable production practices. The use of precision horticulture techniques is more sustainable than conventional to intensive farming methods. Among the various eco-friendly inputs, plant biostimulants are highly effective and can enhance plant growth and production as well as mitigate the adverse effects of abiotic stressors. Protein Hydrolysates (PHs) are a significant class of plant biostimulants based on amino acid and peptide mixtures. Because of their beneficial effects on crop performance, PHs has drawn increased amounts of attention recently. Compared with other biostimulants microbial biostimulants are more prevalent in crop production. A new approach is the formulation of a mixture of plant growth-promoting microorganisms/microbe-derived metabolites and protein hydrolysates as single biostimulants, to nourish the soil, plants and microbes. This review presents a thorough summary of recent research on the postulated modes of action of PHs and microbial biostimulants in horticultural crops. Furthermore, this study highlights the potential of protein hydrolysates and microbial biostimulants and the potential of the protein-rich microbial biostimulants to make horticulture more profitable and to safeguard the environment.